Health information technology use among older adults in the United States, 2009–2018. (3rd May 2020) - Hung, Li-Yu; Lyons, Jennifer G.; Wu, Chung-Hsuen
Abstract: Objectives: The purpose of this study was to assess (1) the trends of and (2) the factors associated with health information technology (HIT) use among older adults in the U.S. Methods: A decade (2009–2018) of data from the U.S. National Health Interview Survey (NHIS) was used. The trends of HIT use among older adults (aged 65 over) were reported and compared to younger adults (aged 18–64) using weighted percentages adjusted by NHIS complex sampling design. HIT use, which was assessed with five questions asking whether respondents used the internet to (1) look up health information, (2) use chat groups to learn about health topics, (3) fill a prescription, (4) schedule medical appointments, and (5) communicate with health care providers by email. Andersen's Behavioral Model of Health Services Use was used to select and categorize the covariates. Multivariable logistic regression models were conducted to identify the predictors of HIT use. Results: The prevalence of HIT use significantly increased from 9.3 million (24.8% of the 37.3 million older adults) in 2009 to 22.3 million (43.9% of the 50.9 million older adults) in 2018 ( p < .01). Among U.S. older adults, young-older, white females, higher education, higher income, insurance coverage, and good health status were more likely to report HIT use. Conclusions: This study found an increasing trend of HIT use among older adults in the U.S. from 2009 to 2018. Healthcare providers should be conscious of older adults' increased HIT use patterns and guide them to proper health management.